First-Session Therapeutic Relationship and Outcome in High Risk Adolescents Intensive Group Psychotherapeutic Programme - Hauber, Kirsten; Boon, Albert (Frontiers in Psychology, 2022)
Background An important determinant of therapy outcome is the quality of the therapeutic relationship. This study evaluated the association between the client’s assessment of first-session therapeutic relationship (FSTR) and outcome in an intensive treatment for adolescents with personality disorders. Method Patients (N = 92) were measured weekly during intensive group treatment. The therapeutic relationship was measured with the Child version of the Session Rating Scale (C-SRS) that was completed after each group therapy session by the patient. Outcome was measured with the Child version of the Outcome Rating Scale (C-ORS). Reliable change index (RCI) was calculated for the both instruments to determine significant changes in therapeutic relationship and outcome. Results A good FRST gave twice as much chance of a significantly better outcome. Especially for those with moderate FSTR, establishing and maintaining a good working relationship during treatment could increase the chances of a good outcome considerably. In contrast, adolescents with low FSTR had little chance of positive outcome regardless of any improvement in the therapeutic relationship. Conclusion Adolescents assessment of FRST is indicative of the chance of a good outcome.